2020
DOI: 10.1017/s0025315419001243
|View full text |Cite
|
Sign up to set email alerts
|

Mono- vs multifilament gillnets: effects on selectivity of narrow-barred Spanish mackerel Scomberomorus commerson in the Persian Gulf

Abstract: Iranian coastal fishers targeting narrow-barred Spanish mackerel (Scomberomorus commerson) recently replaced their historical multifilament gillnets with those made from monofilament, evoking management concerns over potential increases in catch-per-unit-of-effort. During 20 fishing days, we compared catches from replicate surface-set gillnets that were identical in terms of mesh size (140 mm stretched opening), length (180 m), depth (30 m), hanging ratio (0.56) and spatio-temporal deployment, but had differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Possible solutions for maintaining consistent size selectivity throughout the entire fishing year might encompass some of the key technical factors known to affect gillnet catches, including reducing hanging ratio (Gray et al ., 2005), increasing mesh size (Hamley, 1975), or alternative materials (Eighani et al ., 2020). For example, several studies have revealed negative relationships between gillnet hanging ratios and selectivity or efficiency (Gray et al ., 2005), including for similar-shaped pelagic species (Samaranayka et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Possible solutions for maintaining consistent size selectivity throughout the entire fishing year might encompass some of the key technical factors known to affect gillnet catches, including reducing hanging ratio (Gray et al ., 2005), increasing mesh size (Hamley, 1975), or alternative materials (Eighani et al ., 2020). For example, several studies have revealed negative relationships between gillnet hanging ratios and selectivity or efficiency (Gray et al ., 2005), including for similar-shaped pelagic species (Samaranayka et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case in Iran, where artisanal gillnetters target S. commerson for nine months each year during the species’ regional migration from October (autumn) to June (spring/summer), after which fishing effort shifts to other species (Eighani et al ., 2020). The sizes of S. commerson caught by Iranian gillnetters typically range from 50 to 120 cm FL and encompass means at 50% maturity of ~67 and 80 cm FL for females and males, respectively, or 1–2-year-old fish (Roa-Ureta et al ., 2019; Eighani et al ., 2020). Peak catches often coincide with spawning during late spring (May and June) (Claereboudt et al ., 2005; Roa-Ureta et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Length of capture was analysed for each species by comparing the proportion retained from the catch between treatments in each length class following the methods of Holst and Revill (2009) and Eighani, Bayse, Paighambari and Broadhurst (2020). The logit (baited/baited + non‐baited) of the catches‐at‐length was estimated by low‐order polynomial GLMMs (degree 0–4), and the data were fitted as a quasi‐likelihood model within a binomial distributed model using the glmmPQL function.…”
Section: Methodsmentioning
confidence: 99%